Pengaruh Pendapatan Asli Daerah Terhadap Pertumbuhan Ekonomi di Provinsi Sulawesi Tengah Periode 2015-2019 - Ramla Ilham Darise (Jurnal Multidisiplin Madani, 2022)
This study aims to determine and analyze the Effect of Regional Original Income on Economic Growth in Central Sulawesi Province for the 2015-2019 Period. The instrument used in this study is a ratio scale with multiple linear regression analysis techniques. The results of multiple linear analysis show that Regional Original Income has an effect on Economic Growth, Regional Taxes have an effect on Economic Growth, Regional Levies have an effect on Economic Growth, Results of Separated Regional Wealth Management have no effect on Economic Growth, Other Legitimate Regional Original Income has an effect on Economic Growth in Regencies/Cities in Central Sulawesi for the 2015-2019 Period. Regional Taxes, Regional Retributions, Results of Separated Regional Wealth Management and Others PAD Which together or simultaneously affect Economic Growth in Regencies/Cities in Central Sulawesi for the 2015-2019 Period.